Integrating Community-Based Inquiry and Students´ Sense of Belonging to Develop English Writing Skills - P, Jeffrey Rodolfo Unate; Rubiano, Deyssi Acosta (International Journal of Membrane Science and Technology, 2023)
This study reports an action research on the effects of using community-based inquiry as a strategy to develop writing skills with 35 ninth-grade public school students. Data were collected through the application of a teacher´s diary, a writing diagnostic test, and four questionnaires, which were analyzed in the light of mixed methods. The findings revealed that the students retrieved existing information dealing to isolated vocabulary to creatively connect them with their writing process, they worked on building positive relationships through the guided and peer writing correction exercises, and by the engaging experience with the community inquiry, the participants of this research study supported their narrative sequencing, and knowledge of grammar. In conclusion, the study showed that the use of Community-Based Inquiry in combination with a sense of belonging, feedback, and correction produced meaningful effects on the development of learners’ writing skills.